Embezzlement infrastructure investment in Colombia (2014)
Corruption creates fatal squeals in any country in its economy, democracy and society. In Colombia the results of this scourge are catastrophic infrastructure, creating a major obstacle to development. The government is making efforts to punish and reduce this scourge, but institutions are weak, corruption still has a very strong arm in the country's politics, because the prevention must come from the most intimate of both the institutions and officials that shape. Another important part of this link is the community, which also has the task of monitoring officials who represent them.